Respuesta :

Answer:

  • (-1, 7, - 4)
  • (1, -1, 4)

=====================

Given system

  • x² + z² = 17
  • 4x + y = 3
  • y + z = 3

Rearrange the last two equation

  • 4x = 3 - y
  • z = 3 - y

This gives us:

  • z = 4x

Substitute the value of z into fist equation

  • x² + (4x)² = 17
  • x² + 16x² = 17
  • 17x² = 17
  • x² = 1
  • x = 1 and x = - 1

Find values of z and y

  • x = 1     ⇒ z = 4*1 = 4         ⇒  y = 3 - 4 = - 1
  • x = - 1   ⇒ z = 4*(-1) = - 4    ⇒ y = 3 - (-4) = 7

Answer:

[tex](x,y,z)=\left(\; \boxed{-1,7,-4} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y,z)=\left(\; \boxed{1,-1,4} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

Step-by-step explanation:

Given system of equations:

[tex]\begin{cases}x^2+z^2=17\\\;4x+y=3\\\;\;\;y+z=3\end{cases}[/tex]

To solve by the method of substitution, first rearrange the third equation to make y the subject:

[tex]\implies y=3-z[/tex]

Substitute this into the second equation and solve for z:

[tex]\begin{aligned}\implies 4x+(3-z)&=3\\3-z&=3-4x\\-z&=-4x\\z&=4x\end{aligned}[/tex]

Substitute the found expression for z into the first equation and solve for x:

[tex]\begin{aligned}\implies x^2+(4x)^2&=17\\x^2+16x^2&=17\\17x^2&=17\\x^2&=1\\x&=\pm1\end{aligned}[/tex]

Substitute the found values of x into the second equation and solve for y:

[tex]\begin{aligned}\implies x=-1 \implies 4(-1)+y&=3\\-4+y&=3\\y&=7\end{aligned}[/tex]

[tex]\begin{aligned}\implies x=1 \implies 4(1)+y&=3\\4+y&=3\\y&=-1\end{aligned}[/tex]

Substitute the found values of x into the derived expression for z and solve for z:

[tex]\begin{aligned}\implies x=-1 \implies z&=4(-1)\\z&=-4\end{aligned}[/tex]

[tex]\begin{aligned}\implies x=1 \implies z&=4(1)\\z&=4\end{aligned}[/tex]

Therefore, the solutions are:

[tex](x,y,z)=\left(\; \boxed{-1,7,-4} \; \right)\quad \textsf{(smaller $x$-value)}[/tex]

[tex](x,y,z)=\left(\; \boxed{1,-1,4} \; \right)\quad \textsf{(larger $x$-value)}[/tex]

ACCESS MORE